Digital Marketing for Micro Businesses in Tenrigangkae Village Through Shopee and Instagram - Rahmawati; Muhammad Ammar Naufal; Muhammad Ikram; Alimuddin (LPP Chani, 2025)
The development of digital technology has opened up great opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their markets through digital-based marketing strategies. However, MSME players in Tenrigangkae Village still face limitations in digital literacy, social media utilization, and marketplace management. This community service article aims to improve the digital marketing capacity of MSME actors through a Participatory Action Research (PAR) approach that emphasizes active participation in every stage. The activities carried out include an initial survey, discussions with partners, as well as socialization and assistance in creating Instagram and Shopee accounts. This community service article shows an increase in the understanding and skills of MSME players in managing social media, uploading products, editing photos, and developing more effective promotional strategies. This program not only increases the competitiveness of MSMEs locally but also opens up marketing opportunities to a wider market. This community service article concludes that practice-based mentoring can have a tangible impact on SME development and has the potential to be replicated in other regions with similar contexts.